3 Efektivitas Dalam Pengawasan Asrama Sma Negeri Keberbakatan Olahraga Provinsi Bengkulu - Ayu, Puja Putri; Lorita, Evi; Handayani, Tuti; Sariningsih, Marida (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This research aims to describe the Effectiveness in Supervision of SMANKO Dormitory in Bengkulu Province. The approach in this research uses a descriptive qualitative approach. Data collection techniques were conducted by interview and documentation. Data analysis techniques used include data reduction, data presentation (data display) and conclusion drawing/verification. The results showed that, from the results of interviews and discussions about